Adsorpsi Logam Tembaga (Cu), Mangan (Mn) dan Nikel (Ni) dalam Artificial Limbah Cair dengan Menggunakan Nanopartikel Magnetit (Fe3O4) - Diah Mahmudah; Nurhidayati Sakinah; Edi Suharyadi (Department of Physics, Sebelas Maret University, 2017)
Magnetite (Fe3O4) nanoparticles have been successfully synthesized using co-precipitation method and have been used for removing Cu, Mn and Ni metals ions from artificial wastewater. Ability of removing metal ions with Fe3O4 against pH, adsorbent particle size, readsorption and by addition of Polyethylene Glycol (PEG-4000) as coating agent of adsorbent have been studied. The adsorption process was found to be pH-dependent. Maximum adsorption at pH 12 for most of the metal ions with percent of sorption Cu 99.79%, Ni 69.83% and Mn 44.53%. Using adsorbent with 12 nm of particles size, readsorption process and by addition of Polyethylene Glycol (PEG-4000) as coating agent of adsorbent also made the ability of removing metals ions increasing. Preliminary results indicate that magnetite nanoparticles may be used as an adsorbent for removal of Cu, Mn and Ni from wastewater.